Socioeconomic development of Mexico between 2010 and 2020 and economic and trade relations with Brazil and the United States. - Pedro Barbosa de Lima Neto; Thaís Guimarães Alves (Universidade Estadual de Alagoas, 2023)
The present work aims to present the economic and trade relationship between Mexico and the United States in the period 2010-2020 and to elucidate how an approximation between Mexico and Brazil, through South-South Cooperation, could occur. Due to the dynamics of Mexico's relations with the United States, where most imports and exports have their origin and destination to and from US soil, a rapprochement between Mexico and Brazil is important since it can end this relationship of dependence, given that the relations of the two Latin American countries are not close. Thus, the methodology will be hypothetical-deductive since the work will be developed from a possible dependence of Mexico with the United States to answer if there is, in fact, a relationship of economic dependence between them and how it occurs, and how an approximation in economic relations between Mexico and countries of the global South, especially Brazil, can benefit both and help to end such dependence.